Czynności egzekucyjne w świetle ustawy o postępowaniu egzekucyjnym w administracji - Drelichowska, Angelika (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The article analyses a difficult and complex problem of enforcement actions in the light of Polish Act on the Enforcement Proceedings in Administration. The author stresses that in the doctrine of enforcement proceedings in administration there is no agreement with regards to this problem and the meaning of the term “enforcement action.” Taking this circumstance into account the author determines the main objective of the paper as creating her own concept of enforcement actions based on legal provisions, opinions expressed in legal doctrine as well as her own scientific observations.As a result of the scientific research the author reaches a conclusion that every enforcement action has to fulfill two prerequisites. The first prerequisite is that this action has to be taken by enforcement authority. The second is that the goal of every enforcement action is application or fulfillment of enforcement remedy. Therefore the definition of enforcement action is based on two criteria: subjective criterion and objective criterion.An analysis of the norms concerning enforcement proceedings in administration shows that the legal action which does not fulfill the aforementioned prerequisites cannot be defined as an enforcement action but only a procedural action in enforcement proceedings in administration.
Keywords: czynności egzekucyjne; ustawa o postępowaniu egzekucyjnym w administracji